The discovery of excellence: The assets of exemplars in business ethics - deVries, Paul (Journal of business ethics, 1986)
Exemplars, or concrete problems and resolutions, play a far more central role in business ethics than do detailed rules. Exemplars, such as case studies, anecdotes, parables, and fables, are nearly as important as general ethical principles., There are four arguments for recognizing this essential role for exemplars in business ethics. First, exemplars facilitate impartial agreement where agreement on detailed moral rules eludes us. Second, exemplars uniquely facilitate, for the purposes of training and decision making, the balanced integration of diverse sets of values. Third, the use of exemplars appropriately cultivates personal judgment, making detailed moral roles useful in exceptional cases only. Fourth, exemplars provide the flexibility necessary for making moral decisions within the continued flux of responsible business life.